Implementasi Program Makanan Sehat dan Halal di SMK Ibnu Khaldun Balikpapan sebagai Upaya Peningkatan Kesadaran Gizi Siswa - Zeny Lilla Mewaty; Mursalim Mursalim; Muhammad Birusman N (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the implementation of healthy and halal food in schools, particularly at SMK Ibnu Khaldun Balikpapan. The background of this research is driven by the importance of consuming food that meets health and halal standards in forming a healthy lifestyle in accordance with Islamic law. The research method used is a descriptive quantitative approach with a survey technique through questionnaires administered to 100 students in grades X and XI. The results of the study indicate that students' awareness of the importance of healthy and halal food is relatively high, although there are still challenges in its comprehensive implementation, particularly in terms of school canteen supervision and regular education. These findings serve as an important basis for school authorities and policymakers to design more intensive programs to promote the adoption of healthy and halal eating habits.